Sociodemographic and clinical predictors of adherence to antidepressants in depressive disorders: a systematic review with a meta-analysis - Del Pino-Sedeño, Tasmania; Infante-Ventura, Diego; Hernández-González, Diego; González-Hernández, Yadira; González de León, Beatriz; Rivero-Santana, Amado; Hurtado, Isabel; Acosta Artiles, Francisco Javier (Frontiers in Pharmacology, 2024)
Current evidence reveals concerning rates of non-adherence to antidepressant treatment, possibly influenced by various relevant determinants such as sociodemographic factors or those related to the health system and their professionals. The aim of this paper is to review the scientific evidence on sociodemographic and clinical predictors of adherence to pharmacological treatment in patients diagnosed with a depressive disorder.Methods: a systematic review (SR) was conducted. The search for a previous SR was updated and de novo searches were performed in Medline, EMBASE, Web of Science (WoS) and PsycInfo (last 10 years). The risk of bias was assessed using the Cochrane tool for nonrandomized studies -of Exposure (ROBINS-E). Meta-analyses were conducted.Results: Thirty-nine studies (n= 2,778,313) were included, 24 of them in the meta-analyses. In the initiation phase, no association of adherence was found with any of the predictors studied. In the implementation and discontinuation phases, middle-aged and older patients had better adherence rates and lower discontinuation rates than younger ones. White patients adhered to treatment better than African-American patients.Discussion: Age and ethnicity are presented as the predictive factors of pharmacological adherence. However, more research is needed in this field to obtain more conclusive results on other possible factors.